2015
DOI: 10.2298/zmspn1529017s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar application on morphological traits in maize and soybean

Abstract: This paper analyses the effects of the biochar application morphologi?cal traits in maize and soybean under semi-controlled conditions. During the study, the in?creasing doses of biochar (0%, 0.5%, 1, 3, and 5%) were incorporated in three soil types: Alluvium, Humogley and Chernozem to determine plant height and shoot weight. The ex?periment was set up as fully randomized design with three repetitions. The plants were grown in pots of 5 l with controlled watering and N fertilization. The rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Sun et al [41] suggested that biochar incorporation to brown soil can benefit soybean production by N retention in the soil and enhanced microbial turnover that resulted in P and K feedback. Results obtained by Seremesic et al [40] correspond with a study of Yin et al [42] on acid black soil, in which soybean yield increased by 35.97% compared to the control. Significant effects of biochar application on the soybean shoot were observed on Humogley soil compared to soybean height that was observed on Chernozem.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Sun et al [41] suggested that biochar incorporation to brown soil can benefit soybean production by N retention in the soil and enhanced microbial turnover that resulted in P and K feedback. Results obtained by Seremesic et al [40] correspond with a study of Yin et al [42] on acid black soil, in which soybean yield increased by 35.97% compared to the control. Significant effects of biochar application on the soybean shoot were observed on Humogley soil compared to soybean height that was observed on Chernozem.…”
Section: Discussionsupporting
confidence: 77%
“…Seremesic et al [40] tested the effect of biochar at various doses (12.5, 25.75, 125 t ha −1 ) and different soil types (Alluvium (A), Chernozem (C), and Humogley) on the biometric parameters of soybeans. The authors showed that soybean shoot biomass was significantly affected by soil type and biochar level.…”
Section: Discussionmentioning
confidence: 99%
“…Due to mobile nature of nitrogen, it moves to the grains after its uptake resulting in enhanced kernel weight and yield. The above results lie in par with [19,20] who reported that combination of biochar with inorganic fertilizers had a significant effect on maize yield and development [21,22] also received positive response from plant yield when they applied organic manures in combination with inorganic fertilizers.…”
Section: Discussionsupporting
confidence: 62%